1979
DOI: 10.1104/pp.63.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Cell-free Translation of Total Messenger RNA from Germinating Castor Bean Endosperm

Abstract: Polyadenylated RNA was isolated from the total RNA fraction extracted from the endosperm tissue of 3-day-old castor bean seedlings by affinity chromatography on oligo(dT)-cellulose. This polyadenylated RNA was efficiently translated into protein when added to a messenger RNA-dependent cell-free system derived from rabbit reticulocytes. Characterization of the translational products by electrophoresis followed by autoradiography established that numerous discrete polypeptides were formed with molecular weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The total RNA preparation obtained was clear, rapidly dissolved and did not subsequently clog the affinity chromatography column. The absorption spectra and the yield (2 mg total RNA per g fresh weight, or 0.2%) were in agreement with published data (5). Total RNA was fractionated on a column of oligo-(dT)-cellulose, generally yielding 1% poly(A) RNA, regardless of the sex.…”
Section: Isolation and Characterization Of Total Rnas Poly(a) Rnas supporting
confidence: 68%
“…The total RNA preparation obtained was clear, rapidly dissolved and did not subsequently clog the affinity chromatography column. The absorption spectra and the yield (2 mg total RNA per g fresh weight, or 0.2%) were in agreement with published data (5). Total RNA was fractionated on a column of oligo-(dT)-cellulose, generally yielding 1% poly(A) RNA, regardless of the sex.…”
Section: Isolation and Characterization Of Total Rnas Poly(a) Rnas supporting
confidence: 68%
“…Endogenous nucleases from numerous plant sources frequently have been reported to be a problem during polysome isolations. Recently, Lord and co-workers (4) have reported degradation problems when attempting to isolate intact polysomes from castor bean endosperm.…”
Section: Resultsmentioning
confidence: 99%
“…The same study (4) found that a substantial proportion of the poly(A)+ RNA was engaged with bound ribosomes. Additionally, poly(A)+ RNA increased in phase with cellular organelle content (4). The fact that all organelles proliferate rapidly and that the modes of segregation and synthesis of their various matrix enzymes may be analogous, strongly suggests that the polyribosome populations may be uniquely and discretely segregated on the ER.…”
mentioning
confidence: 89%
See 2 more Smart Citations